Gut metagenome associations with extensive digital health data in a volunteer-based Estonian microbiome cohort - Aasmets, Oliver; Krigul, Kertu Liis; Lüll, Kreete; Metspalu, Andres; Org, Elin (Nature communications, 2022)
Microbiome research is starting to move beyond the exploratory phase towards interventional trials and therefore well-characterized cohorts will be instrumental for generating hypotheses and providing new knowledge. As part of the Estonian Biobank, we established the Estonian Microbiome Cohort which includes stool, oral and plasma samples from 2509 participants and is supplemented with multi-omic measurements, questionnaires, and regular linkages to national electronic health records. Here we analyze stool data from deep metagenomic sequencing together with rich phenotyping, including 71 diseases, 136 medications, 21 dietary questions, 5 medical procedures, and 19 other factors. We identify numerous relationships ( n = 3262) with different microbiome features. In this study, we extend the understanding of microbiome-host interactions using electronic health data and show that long-term antibiotic usage, independent from recent administration, has a significant impact on the microbiome composition, partly explaining the common associations between diseases. Here, the authors present results of the Estonian Microbiome Project, which combines metagenomics and electronic health data from 2500 individuals, expanding microbiome-host interactions in particular with regards to effects of long-term antibiotic usage on the microbiome across diseases.